EVALUASI EFEKTIVITAS PROGRAM KOMUNIKASI PUBLIK DINAS KOMUNIKASI DAN INFORMATIKA DIY DALAM MENJANGKAU BERBAGAI KALANGAN MASYARAKAT - Erik Prananda Sahputra; Susatyo Herlambang (JMMU: JURNAL MAHASISWA MANAJEMEN DAN UMUM, 2024)
Currently, in the midst of the digitalization era, the use of social media is popular among Indonesian people. Both parents and teenagers are very active in using social media, even in daily activities, social media has become an essential need for some people. As a very effective tool, social media is used to spread information in various circles. Social media has become a communication platform used by various segments of society, especially teenagers, students, celebrities, as well as state officials such as presidents, legislative members and political parties. They use social media as a means to hear people's aspirations. In fact, society which previously tended to be conservative and reluctant to accept change or new technology, is now starting to open up to technological progress. Diskominfo DIY's social media, such as Website, Instagram, Facebook, Twitter and YouTube, continue to play a role in providing the latest information to encourage Public Information Openness. The information published via social media does not only come from internal sources, but also includes all activities carried out by the DIY Government in various fields, which are routinely uploaded periodically. One of the main challenges in public communication is how effectively to convey relevant and useful messages to various groups of society. Every level of society has different communication needs and preferences, so inclusive and diverse communication strategies are needed to reach all levels of society.